Artificial Sweeteners Versus Regular Mixers Increase Breath Alcohol Concentrations in Male and Female Social Drinkers. (6th December 2012) - Marczinski, Cecile A.; Stamates, Amy L.
<x xml:space="preserve">Abstract</x> Background Limited research suggests that alcohol consumed with an artificially sweetened mixer (e.g., diet soft drink) results in higher breath alcohol concentrations (BrACs) compared with the same amount of alcohol consumed with a similar beverage containing sugar. The purpose of this study was to determine the reliability of this effect in both male and female social drinkers and to determine if there are measureable objective and subjective differences when alcohol is consumed with an artificially sweetened versus sugar‐sweetened mixer. Methods Participants (n = 16) of equal gender attended 3 sessions where they received 1 of 3 doses (1.97 ml/kg vodka mixed with 3.94 ml/kg Squirt, 1.97 ml/kg vodka mixed with 3.94 ml/kg diet Squirt, and a placebo beverage) in random order. BrACs were recorded, as were self‐reported ratings of subjective intoxication, fatigue, impairment, and willingness to drive. Objective performance was assessed using a cued go/no‐go reaction time task. Results BrACs were significantly higher in the alcohol + diet beverage condition compared with the alcohol + regular beverage condition. The mean peak BrAC was 0.091 g/210 l in the alcohol + diet condition compared with 0.077 g/210 l in the alcohol + regular condition. Cued go/no‐go task performance indicated the greatest impairment for the alcohol + diet beverage condition. Subjective measures indicated that participants appeared unaware of any differences in the 2 alcohol conditions, given that no significant differences in subjective ratings were observed for the 2 alcohol conditions. No gender differences were observed for BrACs, and objective and subjective measures. Conclusions Mixing alcohol with a diet soft drink resulted in elevated BrACs, as compared with the same amount of alcohol mixed with a sugar‐sweetened beverage. Individuals were unaware of these differences, a factor that may increase the safety risks associated with drinking alcohol.